Interference between face and non-face domains of perceptual expertise: a replication and extension - Curby, Kim M.; Gauthier, Isabel (Frontiers in Psychology, 2014)
As car expertise increases, so does interference between the visual processing of faces and that of cars; this suggests performance trade-offs across domains of real-world expertise. Such interference between expert domains has been previously revealed in a relatively complex design, interleaving 2-back part-judgment task with faces and cars (Gauthier, Curran, Curby, & Collins, 2003). However, the basis of this interference is unclear. Experiment 1a replicated the finding of interference between faces and cars, as a function of car expertise. Experiments 1b and 2 investigated the mechanisms underlying this effect by 1) providing baseline measures of performance and 2) assessing the specificity of this interference effect. Our findings support the presence of expertise-dependent interference between face and non-face domains of expertise. However, surprisingly, it is in the condition where faces are processed among cars with a disrupted configuration where expertise has a greater influence on faces. This finding highlights how expertise-related processing changes also occur for transformed objects of expertise and that such changes can also drive interference across domains of expertise.